2021
DOI: 10.1021/acsomega.1c04618
|View full text |Cite
|
Sign up to set email alerts
|

Porous Carbon Nanofibers with Heteroatoms Doped by Electrospinning Exhibit Excellent Acetone and Carbon Dioxide Adsorption Performance: The Contributions of Pore Structure and Functional Groups

Abstract: Rich chemical properties and a well-developed pore structure are the key factors of porous materials for gas storage. Herein, rich heteroatom-doped porous carbon nanofibers (U1K2-X) with a large surface area were prepared by electrospinning followed by potassium hydroxide (KOH) activation. Low-cost urea was chosen as the nitrogen source and structural guiding agent. U1K2-X have a high specific surface area (628–2688 m2 g–1), excellent pore volume (0.468–1.571 cm3 g–1), and abundant nitrogen (2.5–12.8 atom %) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Because of the highly feasible dipole–quadruple interaction between CO 2 and other adsorption sites (host–guest interaction), the interaction between CO 2 molecules becomes very negligible, which correlates with the Langmuir isotherm used for the fitting of the adsorption curve. Notably, all the Tt-POPs were rich in heteroatom content; here, micropores and the narrow PSD play a crucial role in enhancing the CO 2 uptake capacity. , From the PSD analysis (Figure S14, Supporting Information), it is obvious that among all the POPs, Tt-POP-2 showed a narrow PSD accompanied by 0.40 cm 3 /g of pore volume compared to the other Tt-POPs consisting of broader ones. This reflected the CO 2 uptake efficiency, and eventually Tt-POP-2 exhibited the best CO 2 uptake capacity in comparison to its other counterparts.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Because of the highly feasible dipole–quadruple interaction between CO 2 and other adsorption sites (host–guest interaction), the interaction between CO 2 molecules becomes very negligible, which correlates with the Langmuir isotherm used for the fitting of the adsorption curve. Notably, all the Tt-POPs were rich in heteroatom content; here, micropores and the narrow PSD play a crucial role in enhancing the CO 2 uptake capacity. , From the PSD analysis (Figure S14, Supporting Information), it is obvious that among all the POPs, Tt-POP-2 showed a narrow PSD accompanied by 0.40 cm 3 /g of pore volume compared to the other Tt-POPs consisting of broader ones. This reflected the CO 2 uptake efficiency, and eventually Tt-POP-2 exhibited the best CO 2 uptake capacity in comparison to its other counterparts.…”
Section: Resultsmentioning
confidence: 95%
“…Notably, all the Tt-POPs were rich in heteroatom content; here, micropores and the narrow PSD play a crucial role in enhancing the CO 2 uptake capacity. 59,60 From the PSD analysis (Figure S14, Supporting Information), it is obvious that among all the POPs, Tt-POP-2 showed a narrow PSD accompanied by 0.40 cm 3 /g of pore volume compared to the other Tt-POPs consisting of broader ones. This reflected the CO 2 uptake efficiency, and eventually Tt-POP-2 exhibited the best CO 2 uptake capacity in comparison to its other counterparts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally, a suitable pore structure and surface functional groups of adsorbents can promote the adsorption performance of CO 2 . For instance, researchers 99 have reported that narrow micropore size (0.8 nm) is the key factor for CO 2 adsorption. In addition, pore volume are the key factors for CO 2 adsorption.…”
Section: Polymeric Membranesmentioning
confidence: 99%
“…Similar way, CO 2 adsorption by activated carbon nanofibers prepared from PAN, PVDF, and melamine was reported by a number of authors with adsorption in the range 0.55-3.47 mmol g À1 at 25 °C. Shi et al [95][96][97][98][99][100] studied acetone and CO 2 adsorption properties of porous carbon nanofibers prepared from PAN and reported acetone adsorption capacity of 955.74 mg g À1 and CO 2 adsorption of 3.34 mmol g À1 at 25 °C. Storage of hydrogen gas by electrospun nanofibers, being the main focus of this paper, is presented below in separate sections.…”
Section: Adsorption Of Methane Carbon Dioxide Acetone and Other Gases...mentioning
confidence: 99%